Scleral pockets for an innovative technique of intrascleral fixation of intraocular lens. Issue 5 (September 2020) - Postorino, Maurizio; Meduri, Alessandro; Inferrera, Leandro; Tumminello, Giuseppe; Rechichi, Miguel; Caparello, Ottavio; Aragona, Pasquale
The aim of this article is to report the results of an innovative technique for a scleral fixation of a posterior chamber intraocular lens using our new modified technique. We retrospectively reviewed the medical records of 15 eyes of 15 patients who underwent sutureless intrascleral intraocular lens fixation using our modified technique. We used a 23-gauge knife to perform sclerotomy and create two parallel scleral pockets for the haptics. The mean follow-up period was 3 years (3 ± 1). No complications were detected during the follow-up period. The creation of two parallel scleral pockets, parallel to the limbus, greatly simplifies the introduction of intraocular lens haptics.